Structural Analysis of The Short Story “Hantu Mbah Darmo” - Nurmalasari; Sartika; Intan Lukmawati; Lailatul Fitriyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze short stories using a structural analysis approach, which highlights intrinsic elements such as theme, characters, characterization and setting that play a role in building the meaning of the story. This short story tells the phenomenon of the appearance of “Hantu Mbah Darmo” in a Javanese village, which creates shared fear and various speculations in society. The analysis shows that the main theme of this story is collective fear that arises due to belief in myths and mystical things. The characters are depicted facing a dilemma between traditional beliefs and rational thinking, which reflects the dynamics of the community's culture. The traditional Javanese village setting strengthens the atmosphere of the story. The use of local languages ​​​​adds depth to the cultural values ​​​​in the narrative. This study concludes that “Hantu Mbah Darmo” not only raises stories about the mystical world, but also describes the socio-cultural dynamics of society that are still strongly connected to tradition. This structural approach provides an understanding of how literature reflects the social, cultural, and collective psychological realities of society.